CATALÁ GORGUES, J.I.; ROS GALIANA, F. (2020). Senderos de la descripción. Perspectivas teóricas y prácticas diversas. Granada: Editorial Comares - López Martínez, Gabriel (Daimon, 2023)
Reseña del libro: CATALÁ GORGUES, J.I.; ROS GALIANA, F. (2020). Senderos de la descripción. Perspectivas teóricas y prácticas diversas. Granada: Editorial Comares.